UNIFICATION OF ISLAM AND DAYAK NGAJU: SYMBOLIC DA'WAH ON THE GARING BATANG MOTIF HEADSCARF FROM THE BORNEO HIJAB BRAND - Ahmadi, Ahmadi; Lestari, Mega Asri (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Modern era da'wah strategies are increasingly diverse, one of which comes from the fashion industry which internalizes Islamic teachings through fashion based on local wisdom. This study aims to analyze the symbolic preaching contained in the crisp stem motif on the Borneo Hijab headscarf. There are two aspects that are the focus of the research, namely the philosophical meaning of the garing rod motif and explaining the symbolic preaching contained in the garing rod motif on the Borneo Hijab headscarf. This research uses a qualitative-interpretive method with  a  semiotic  theory  approach.  Data  was  obtained  in  two  ways,  namely, observation  and  literature  study.  The  data  obtained  was  then  analyzed  using Charles Sanders Pierce's triangular theory model, namely signs, representation and interpretation. This study found two important points regarding the meaning of the crisp stem motif on the Borneo Hijab headscarf. First, findings regarding the  philosophical  meaning  of  the  crisp  stem  ornaments  of  the  Borneo  Hijab headscarf.  This  philosophical  meaning  can  be  implemented  in  everyday  life because it concerns human relationships with God, fellow humans and nature. Second, findings regarding symbolic preaching contained in the crisp stem motif on the Borneo Hijab headscarf. There are three classifications of da'wah messages contained in the research object, namely aqidah messages, sharia messages and moral messages.